Calibration of discrete element simulation parameters and threshing test for complete wheat plants - Wang, Shengsheng; Lyu, Weizhen; Jin, Xin; Yu, Shuo; Guo, Hao; Chen, Zhonghan (International Journal of Agricultural and Biological Engineering, 2025)
The existing discrete element model of wheat plants lacks the glume, which hinders the simulation of the entire threshing process. To address this issue, this paper takes wheat at the harvest stage as the research object and constructs a complete discrete element model of wheat plants with glumes based on the Hertz-Mindlin with bonding model in the EDEM simulation software. The parameter calibration of wheat glumes discrete element model is studied through collision bounce experiments, slope experiments, and accumulation experiments. The results show that the coefficient of restitution, coefficient of static friction, and coefficient of rolling friction between glume and steel are 0.488, 0.625, and 0.048, respectively, and the coefficient of restitution, coefficient of static friction, and coefficient of rolling friction between glume and glume are 0.232, 0.966, and 0.059, respectively. The relative errors between the simulation results and the measured values are less than 5%, and the calibration parameters are effective. Based on the structural parameters of the self-developed experiment-bed of tangential axial-flow grain threshing device, a three-dimensional model of the wheat threshing device is established to simulate the whole threshing process of the complete wheat plant, and the bench-scale experiments are carried out with the non-threshing rate as the performance index. The results indicate that the model can completely simulate the separation process of glume and grain and the movement law of different grains, and the relative error of non-threshing rate between the simulation experiments and bench-scale experiments is 4.36%. This further demonstrates that the proposed model can provide a reference for the wheat threshing process research and device performance optimization design.Keywords: discrete element method, wheat plant, glume model, parameter calibration, threshing experimentsDOI: 10.25165/j.ijabe.20251803.9467Citation: Wang S S, Lyu W, Jin X, Yu S, Guo H, Chen Z H. Calibration of discrete element simulation parameters and threshing test for complete wheat plants. Int J Agric & Biol Eng, 2025; 18(3): 12–18.